Axillary surgery in node-positive breast cancer - Nadia Maggi; Rahel Nussbaumer; Liezl Holzer; Walter P. Weber (Breast, 2022)
Long-term follow-up data from multicenter phase III non-inferiority trials confirmed the safety of omission of axillary dissection in selected patients with clinically node-negative, sentinel node-positive breast cancer. Several ongoing trials investigate extended eligibility of the Z0011 protocol in the adjuvant setting. De-escalation of axillary surgery in patients with clinically node-positive breast cancer is currently limited to the neoadjuvant setting, where the sentinel procedure is used to determine nodal pathological complete response. Targeted axillary dissection lowers the false-negative rate of the sentinel procedure, which, however, is consistently associated with a very low risk of axillary recurrence in several recent single-center series. Axillary dissection remains standard care in patients with residual disease after neoadjuvant chemotherapy while the results of Alliance A011202 are pending. The TAXIS trial investigates the role of tailored axillary surgery in patients with clinically node-positive breast cancer, a novel concept designed to selectively remove positive nodes in the adjuvant and neoadjuvant setting.